(untitled) (International Journal of Food and Nutritional Sciences, 2019)
The footwear industry is characterised by intense competition and high customer expectations about product availability and quality. Stores have been working harder in recent years to improve their supply chain operations in order to meet customer demands. Given the critical role supply chain management plays in every retail location’s performance, merchants must optimise their supply chain operations in order to boost customer satisfaction.